Enteral Nutrition Practices and Complications in ICU Settings: A Cross-Sectional Study of Healthcare Professionals’ Perspectives in Saudi Arabia - Zaher S; Alhindi R; Alturki L; Alsobhi E; Alahmadi L; Aldhowayan HA (Journal of Multidisciplinary Healthcare)
Sara Zaher, Reham Alhindi, Layan Alturki, Elaf Alsobhi, Lora Alahmadi, Hadeel Abdulla Aldhowayan Clinical Nutrition Department, College of Applied Medical Sciences, Taibah University, Madinah, Kingdom of Saudi ArabiaCorrespondence: Sara Zaher, Clinical Nutrition Department, College of Applied Medical Sciences, Taibah University, P.O. Box 344, Madinah, 42353, Kingdom of Saudi Arabia, Email Sz332@cam.ac.uk; szaher@taibahu.edu.saBackground: Enteral Nutrition (EN) is the preferred method for providing nutritional support in intensive care units (ICUs) compared to parenteral nutrition (PN) due to its physiological advantages, safety profile, and cost-effectiveness compared to parenteral nutrition (PN). However, evidence suggests that EN might be associated with some complications. In this study, we aimed to identify the most common EN complications, as reported by healthcare professionals (HCPs) working in adult and paediatric ICUs (PICUs) in Saudi Arabia. We also investigated the factors influenced the HCPs’ perception in reporting these EN complications.Methods: In this cross-sectional pilot study, data was collected through an online survey from 25 December 2022 to the end of February 2023. All dietitians, physicians and nurses working in adult and PICUs in Saudi-Arabia were eligible to participate. The survey collected information about the demographic data of the participants, some of the EN related practice in intensive care settings as well as the frequency of the reported EN complications.Results: A total of 173 respondents were included in the study. The most frequently reported complications were diarrhoea [3.06 ± 1.197], aspiration [2.88 ± 1.261], and constipation [2.85 ± 1.11]. A statistical difference was recorded in the frequency of some of the reported EN complications between HCPs working in adults and paediatric ICUs (p< 0.05). The participant’s profession (r=− 2.84, p< 0.05) and years of experience (r=− 0.5, p< 0.05) appeared to statistically influence the perception of HCPs regarding EN complications.Conclusion: This study highlighted the commonly reported complications associated with EN, with differences observed between adult and paediatric settings. The variation in reported complications may be attributed to differences in practitioner characteristics. These findings may emphasize the importance of targeted training, standardized reporting, and evidence-based practices to optimize EN management and improve patient outcomes in ICU settings.Keywords: enteral nutrition, ICU, PICU, EN complications